2006
DOI: 10.1007/s00795-006-0325-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FAK-related non-kinase (FRNK) coincides with morphological change in the early stage of cell adhesion

Abstract: Focal adhesion kinase (FAK), a protein tyrosine kinase, has recently been suggested to play a role in signal transduction through integrins. In fact, FAK is involved in cell proliferation and cell motility by performing signal transduction through integrins. FAK-related non-kinase (FRNK) has been found to be an inhibitor of FAK. As the expression level of FRNK in the cell is very low, the study of FRNK has been preferentially performed by gene overexpression, up to the present, and the role of constitutive FRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The present finding that tumor cells with downregulated FAK activity also became less adherent to the ECM suggests that S-1 is involved in the regulation of FAK phosphorylation. S-1 may lead to downregulation of the expression of certain integrins (29). The results of the present study confirm that systemic administration of S-1 inhibits metastasis of human OSCC cells grafted in the tongue of athymic nude mice.…”
Section: Discussionsupporting
confidence: 83%
“…The present finding that tumor cells with downregulated FAK activity also became less adherent to the ECM suggests that S-1 is involved in the regulation of FAK phosphorylation. S-1 may lead to downregulation of the expression of certain integrins (29). The results of the present study confirm that systemic administration of S-1 inhibits metastasis of human OSCC cells grafted in the tongue of athymic nude mice.…”
Section: Discussionsupporting
confidence: 83%
“…However, previously reported defects during early cell spreading upon FAK inhibition and cell attachment upon FRNK overexpression (Richardson and Parsons, 1996) were not observed here. This may be because cells were able to overcome those effects at the later time points investigated here, or because it is the scaffolding role of FAK that mediates cell spreading, supported by data showing that coexpression of Src or catalytically inactive FAK can rescue cell spreading defects (Richardson et al, 1997) and endogenous FRNK expression is increased during the early stages of cell attachment (Nagoshi et al, 2006), indicating that FAK catalytic activity does not regulate this process. However, we found that pY-binding proteins displayed increased dynamics in IACs upon FAK inhibition, indicating that altered adhesion signaling may be the result of altered dynamics of IAC components rather than changes to IAC composition.…”
Section: Discussionmentioning
confidence: 77%
“…It can upregulate the expression of cyclin D1, a key promoter in cell cycle progression, which accelerates the transition from the G1 to S phase . Overexpression of FAK can facilitate the G1/S phase transition, and one study indicated that the injection of the FAK-related nonkinase (FRNK) mutant in cells suppressed cell proliferation and caused the G1/S phase cell cycle arrest . Moreover, FAK can promote cell cycle progression by activating the Ras-ERK signaling pathway and enhance cell proliferation by disturbing the p53-mediated cell cycle arrest …”
Section: Fak Functions In Cancer Developmentmentioning
confidence: 99%